Pengaruh Penerimaan Diri dan Regulasi Emosi terhadap Psychological Well Being Pasien Kanker - Robertus Surjoseto; Devy Sofyanty (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This explanatory research aims to know the effect of self acceptance and emotional regulation to predict psychological well being cancer patient and to find which one is more effective to predict psychological well being cancer patients. The sampling technique used in this research was convenience sampling technique. Subjects in this research is 100 cancer patient at Dr Cipto Mangunkusumo National Central Public Hospital Jakarta. Data collection was carried out through questionnaires, interviews and observation. Self report technique is used in collecting instrumen data. The data analysis technique used is multiple linear regression analysis processed using Statistical Package for the Social Sciences (SPSS) software. The result shows that there is an influence between self acceptance and emotional regulation in predicting psychological well being where the score of p value F test is 0,000 (p<0,05) and it is found that self acceptance is more effective in predicting psychological well being compare with emotional regulation Based on the research results, the findings are as follows: (1) collectively or simultaneously self acceptance and emotional regulation has a positive and significant effect on psychological well being, (2) partially self acceptance has a positive and significant effect on psychological well being; (3) partially emotional regulation has a positive and significant effect on psychological well being.